Clinico-Pathogenic Pattern of Maxillofacial Cysts – A Dental Health Issue: Maxillofacial Cysts – A Dental Health Issue - Saqulain, Ghulam; Ahmed, Jawwad; Hussain, Altaf; Shahan, Zaimal (Pakistan Journal of Health Sciences, 2024)
Maxillofacial cysts occur frequently and affect dental health. Though majority are asymptomatic, however they can result in disfigurement and affect dental health. Their frequency and clinical characteristics in the local context need to be addressed. Objective: To determine the frequency and clinical characteristics of maxillofacial cysts. Methods: A descriptive retrospective chart review of patients with maxillofacial cysts was conducted at Department of Otorhinolaryngology, Capital Hospital PGMI Islamabad. N= 58 cases of both genders and any age with maxillofacial cysts, who were diagnosed and operated from 1st January 2017 to 31st December, 2018 were studied. Age, gender, clinical features, surgical procedure performed and histological diagnosis were recorded. Data collected were analyzed using SPSS-23.0. Results: Study population revealed a mean age of 28.59+12.37 years and a male: female ratio of 1: 2.22. Dental abscesses were most common (14, 24.1%); followed by mucous retention (12, 20.7%); mucocoele (10, 17.2%); naso-alveolar and dental cysts 8 (13.8%) each; radicular, dentigerous and epidermal inclusion cyst 2 (3.4%) each. The commonest presentation was swelling [46(79.31%)] with right cheek [18(31%)] and left cheek [16(27.6%)] being commonest locations. Denker’s approach was adopted for 6 (10.3%) cases all being naso-alveolar cysts. Caldwell Luc’s approach was adopted for mucocoeles, dental cysts and all the cases of radicular and dentigerous cysts. Conclusions: Maxillofacial cysts are not uncommon, with dental cysts being the commonest cysts of odontogenic origin, mucocoele being commonest cyst of maxillary origin, naso-alveolar cysts arising from the nasolacrimal apparatus and dental abscess being commonest infective pathology.